Mentalidade global e recursos humanos internacionais em empresas brasileiras do setor de construção pesada - Barreto, Maria Simone Prates (2009)
The core objective of this paper is to study the global mindset of managers in Brazilian construction companies. Besides that, there were the specific objectives of reviewing the literature about global mindset and international human resources, identifying the international human resources policies that enable or restrict the development and the maintenance of global mindset among construction companies managers, and characterizing this segment s companies. The research is made of multiple case studies in two organizations, by means of descriptive and qualitative research. The data for analysis was collected by semistructured interviews, besides documents and websites analysis. The selected companies are part of the Brazilian Transnational Companies ranking, made by Fundação Dom Cabral and published in 2009. The research revealed that there is no consistence in the supposition that the studied companies, since they have a large experience accumulated in over 30 years of international presence, have consistent policies of international human resources that can enable the development and the maintenance of their managers global mindset. The analysis of the data pointed out that managers from both companies are in different stages; at Camargo Corrêa, with an ethnocentric orientation, and at Norberto Odebrecht, with a regiocentric or polycentric orientation. Thus, in both cases managers do not present a geocentric view, which is closer to the global mindset. In addition, the research didn t find evidences of the existence of international human resources policies focusing the development and the maintenance of the global mindset, only a few isolated strategies to enable the capacity of thinking globally. Even though the conclusions of this paper cannot be generalized, since this is a study of cases, this can contribute to future studies that seek to understand the global mindset of Brazilian managers and how international human resources policies that develop and maintain the global mindset are used by Brazilian companies